2011
DOI: 10.1103/physrevb.84.205416
|View full text |Cite
|
Sign up to set email alerts
|

Theory of nonequilibrium single-electron dynamics in STM imaging of dangling bonds on a hydrogenated silicon surface

Abstract: During fabrication and scanning-tunneling-microscope (STM) imaging of dangling bonds (DBs) on a hydrogenated silicon surface, we consistently observed halo-like features around isolated DBs for specific imaging conditions. These surround individual or small groups of DBs, have abnormally sharp edges, and cannot be explained by conventional STM theory. Here we investigate the nature of these features by a comprehensive 3-dimensional model of elastic and inelastic charge transfer in the vicinity of a DB. Our ess… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…The DB is then analogous to the island of a single electron transistor, with the tip and substrate forming the source and drain, respectively. Exactly as for a single electron transistor, the electron occupation of the DB is then governed by the electron transfer rates on and off the DB, rather than by equilibrium with the bulk substrate17272829. Further discussion of this phenomenon, together with data illustrating the bias dependence of the depression and enhancement regions are given in Supplementary Note S1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The DB is then analogous to the island of a single electron transistor, with the tip and substrate forming the source and drain, respectively. Exactly as for a single electron transistor, the electron occupation of the DB is then governed by the electron transfer rates on and off the DB, rather than by equilibrium with the bulk substrate17272829. Further discussion of this phenomenon, together with data illustrating the bias dependence of the depression and enhancement regions are given in Supplementary Note S1 and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A single DB (indicated by a red arrow in figures 2(a) and (b)) appears as a bright protrusion in filled states and exhibits the characteristic dark halo surrounding it in empty states [20,22,26,34,40,45,46]. Figure 2(c) shows comparison of typical I(V) spectroscopies acquired on a single DB and the Si:H surface on the 1050°C flashed samples.…”
Section: Minimal Subsurface Dopant Depletion: 1050°c Flashed Samplesmentioning
confidence: 99%
“…The important property allowing such consideration is the DB's quantized charge state levels lying in the silicon bandgap. In fact, a DB can be either empty, singly, or doubly occupied, which corresponds, respectively, to the DB being positive(DB + ), neutral (DB 0 ), or negative(DB -) [20,22,23,26]. This makes conduction through the DB predominantly governed by tunneling rates through its charge states [22,[26][27][28], hence, the quantum dot analogy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Dangling bonds on hydrogen terminated surfaces have been studied extensively for their chemical reactions with organics or metals, diffusion characteristics, and creation mechanisms using scanning tunneling microscopes. 22 Therefore, when investigating the charging character of isolated or coupled DBs, it is critical to know the position of the Fermi level at the surface. [15][16][17][18] Recently, it was shown that dangling bonds on hydrogen terminated silicon surfaces should be considered as single atom quantum dots.…”
Section: Introductionmentioning
confidence: 99%